“Writing it is never ending”: 405 years of readings and silences in a colonial Andean Opera Aperta - Quispe-Agnoli, Rocío (2020)
This essay introduces a collection of scholarly contributions, from inside and outside of Peru, to the study of the Andean colonial world. These essays address once again Guaman Poma de Ayala’s chronicle in its 405thanniversary in 2020. Unknown, invisible, mute for almost 300 years, the ladino Indian’s “letter to the king” reveals itself as a talkative text since its discovery at the Royal Library in Copenhagen, Denmark, at the beginning of the twentieth century. In a bit more than 100 years, Guaman Poma’s work became a talkative text while keeping its enigmatic and cryptic nature. In order to provide a context to the essays that follow, this introduction provides a review of proposed readings related to Guaman Poma’s works in the context of the celebration of its 400th anniversary. It also oﬀers a reﬂection about the open nature of Guaman Poma area studies.